Exploring detailed characteristics of autonomic dysreflexia. (3rd September 2018) - Solinsky, Ryan; Kirshblum, Steven C.; Burns, Stephen P.
Abstract : Objectives: Identify clinical and pathophysiologic insights into autonomic dysreflexia (AD) in patients with spinal cord injury (SCI). Study Design: Analysis of prospectively gathered AD dataset. Setting: Inpatient Veterans Affairs SCI unit. Participants: 78 male patients with SCI who experienced AD. Methods: Statistical methods were utilized to identify the frequency of relative bradycardia vs. tachycardia during AD, the effectiveness of supplemental opioids in managing suspected nociceptive pain mediated AD, the effect of chronicity of SCI on response to pharmacological management of AD, and the response to nitroglycerin ointment in suspected bladder related AD. Results: 445 episodes of AD were analyzed. The frequency of relative bradycardia and tachycardia with AD were 0.3% and 68.0% respectively. The addition of opioids to an antihypertensive medication protocol did not significantly decrease AD episode duration or magnitude of systolic blood pressure (SBP) change. A strongly matched positive linear correlation was identified between the duration of pharmacologically treated AD episodes and chronicity of SCI (R 2 =0.83). Bladder related AD episodes treated with nitroglycerin ointment had a faster onset of action (10.8 minutes vs. 15.9 minutes), faster time to reach a safe target blood pressure (16.5 minutes vs 20.9 minutes), and greater decrease in SBP (84.3mmHg vs. 68.6mmHg) than non-bladder related episodes (P=0.19, 0.23, and 0.02 respectively). Conclusions: AD may commonly occur with relative tachycardia. While further investigation is needed on the effects of chronicity of SCI and pharmacologic management, this study raises multiple directions for future research to understand clinical signs and treatment variables of AD following SCI.